2019
DOI: 10.1002/2211-5463.12581
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of brain‐derived neurotrophic factor (BDNF) expression in sensory neuron axons by miRNA‐206

Abstract: Distinct subcellular localization and subsequent translational control of 3′ UTR variants of mRNA encoding brain‐derived neurotrophic factor (BDNF) are critical for the development and plasticity of neurons. Although the processes that lead to preferential localization of BDNF have been well studied, it is still not clear how neurons ensure differential BDNF production in a spatial‐specific manner. Here, we identified that microRNA (miRNA)‐206 has the potential to specifically regulate BDNF with a long 3′ UTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The Level of miR-206 Is Higher in SI Mice miR-206 has been shown to specifically target long 3 0 UTRs to repress BDNF expression, 9 and we have reported previously that BDNF expression is involved in regulation of impulsive aggression in SI mice. 17 We investigated a role of miR-206 in stress-provoked aggression.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The Level of miR-206 Is Higher in SI Mice miR-206 has been shown to specifically target long 3 0 UTRs to repress BDNF expression, 9 and we have reported previously that BDNF expression is involved in regulation of impulsive aggression in SI mice. 17 We investigated a role of miR-206 in stress-provoked aggression.…”
Section: Resultsmentioning
confidence: 80%
“…8 In dorsal root ganglia, miR-206 specifically targets long 3 0 UTRs to regulate BDNF expression without affecting short 3 0 UTR counterparts. 9 These studies suggest that miR-206 could post-transcriptionally regulate BDNF expression.…”
Section: Introductionmentioning
confidence: 99%
“…Besides DNA methylation and histone modification, microRNAs also contribute to epigenetic modifications in ELS model. For example, overexpression of microRNA-206 in sensory neurons reduces BDNF expression in cell bodies and axons ( Shrestha et al, 2019 ). Another study utilizing ESI in male mice found that ESI susceptible mice had elevated levels of microRNA-206 and reduced BDNF mRNA in the ventral hippocampus compared to controls ( Chang et al, 2020 ).…”
Section: Epigenetic Regulation and Sex Differences In Animal Models Of Major Depressive Disorder Relevant To Social Behaviormentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) critical for the development and plasticity of neurons undergoes transcript-specific regulation by miR-206 inhibiting only an isoform with long 3′UTR without affecting a transcript with a shorter 3′UTR. Such specific regulation led to the decrease of BDNF expression in cell bodies and axons ( 187 ). Another example of transcript-specific 3′UTR with distinct regulation is Nurr1 transcription factor.…”
Section: Common Micrornas In Cancer and Neurodegenerationmentioning
confidence: 99%